급성심근경색에서 Troponin T 와 경색의 크기와의 상관관계 - 서창희; Chang Hee Suh; 김한수; Han Soo Kim; 강한걸; Han Geol Kang; 신준한; Joon Han Shin; 탁승제; Seung Jae Tahk; 이승호; Seong Ho Lee; et al. (The Korean journal of medicine, 1997)
Objectives: The estimation of infarct size has been important in evaluation of prognosis of the patients who had acute myocardial infarction. The infarct size estimated by the thallium-201 SPECT has been known to correlate with the prognosis of patient. The enzymatic estimation by the total release of creatine kinase isoenzyme MB(CK-MB) has been widely used in estimating infarct size clinically, but inconvienent and not cardiospecific. Recently, serum troponin T, cardiospecific myofibrillar protein, has been used in the diagnosis of acute myocardial infarction, and used in the estimation of reperfusion following myocardial infarction. To assess the role of the late troponin T peak concentration on the estimation of infarct size, this prospective study was carried out. Methods: The patients with acute myocardial infarction who were admitted, within 48hours after the onset of chest pain, to Ajou University Hospital between April 1995 and August 1995 were evaluated. All patients were divided into anterior and inferior infarct and checked serum troponin T and CK-MB serially, and underwent stress Thallium-201 SPECT 1 week after infarction, In each group, we assessed the correlation of the late toponin T peak concentration, the total release of CK-MB, and the infarct size estimated by thallium-201 single photon emission computed tomography(SPECT). Results: 1) The eligible subjects consisted of 22 patients (17 men and 5 women), and age ranged from 29 to 77 years(mean 57.8±12.5 years). 2) The mean arrival time to the hospital after the onset of chest pain was 15.5±13.2 hours. The 19 patients had at least one risk factor for coronaryartery disease. 3) The late troponin T peak concentration and the total release of CK-MB in patients with anterior infarction were not different from those with inferior infarction. The infarct size estimated by the thallium-201 SPECT in patients with anterior infarction was larger than patients with inferior infarction The left ventricular ejection fraction in anterio infarction was lower than inferior infarction. 4) The late troponin T peak concentration ha: positive correlation with the infarct size estimated by the thallium-201 SPECT in the total patients, and both patients with anterior infarction and inferio infarction. 5) The total release of CK-MB correlated with the infarct size estimated by the thallium-20 SPECT in the total patients, and the patients of inferior infarction. Conclusion: The late troponin T peak concentration was more accurate than the total release o CK-MB in the estimation of infarct size. Therefore, when the patient arrived to the hospital less than 48hr after the onset of chest pain, the late troponin T peak concentration is useful in the decision and evaluation of therapeutic intervention and in the prediction of prognosis.